INOVASI ALOFLO TISANE BERBASIS BUNGA LIDAH BUAYA: UJI HEDONIK DAN KELAYAKAN USAHA - Elita Aulia; RR. Siti Astuti; Novia Aristi Rahayu (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2026)
ABSTRACT            AloFlo Tisane, an herbal beverage based on aloe vera flowers (Aloe vera), was developed as a functional drink utilizing local bioactive resources. This study aimed to evaluate consumer acceptance and business feasibility of the product. Experimental methods were applied through product formulation and hedonic testing involving 50 untrained panelists assessing color, aroma, taste, and overall preference. Data were analyzed using Independent Sample T-test. Business feasibility was evaluated through cost analysis, cost of goods sold, profit, Break Even Point, and R/C ratio. The results indicated that the formulation with a 1:4:3 ratio of aloe flower, ginger, and sappan wood showed the highest acceptance level. Financial analysis demonstrated a cost of Rp7,576 per unit and a selling price of Rp17,000, indicating profitability and feasibility (R/C ratio > 1). The product shows potential as a functional beverage with economic value.Keywords:  AloFlo Tisane, aloe flower, hedonic test, feasibility, herbal beverage